A Performance of Power System Installation Tool Kits Electricity 1 ɸ and 3 ɸ As Practicum Kits at the Power Electronics Laboratory - Irwansyah Syam; Nuzuli Fitriadi; Lindawati Lindawati; Mukhsan; Isma (Jurnal Inotera, 2020)
A series circuit is a parallel circuit or a circuit system that connects from a voltage source (V) to a load, while a parallel circuit is a branching circuit that connects from a voltage source to a load. The measurement process in the electric power system is one of the standard procedures that must be carried out, because through the measurement, the required quantities will be obtained in accordance with the requirements of PUIL 2000. three phases by making a series and parallel installation circuit. The method used in this research is to test, measure and calculate the value of voltage (V), current (I), resistance (R) and load power (P) in a series of single-phase and three-phase electrical installations in series and parallel. Based on measurements and calculation results, the maximum total current generated in a single phase series circuit installation is 82.57 Ampere, which applies equally to L1, L2, L3 and L4. The maximum total current generated in a parallel circuit is 129.35 Amperes at L1 and a minimum current of 96.29 Amperes at L4. For the maximum real power (P) generated in a single-phase series series installation is 13872 Watts and in parallel circuits is 21523 Watts, for the maximum apparent power (S) generated in a single-phase series series installation is 17339 Watts and in parallel circuits is 26904 Watt. While the maximum total current generated in a three-phase series series installation is 94.33 Amperes, which applies equally to L1, L2, L3 and L4. The maximum total current generated in a parallel circuit is 150.56 Amperes at L1, and a minimum current of 120.17 Amperes is located at L4. For the maximum real power (P) generated in a three-phase series series installation is 34637 Watt and in a parallel circuit is 54876 Watt, while the maximum apparent power (S) generated in a series circuit is 43297 Watt and in a parallel circuit is 68595 Watt.